Chemotherapy Management of Nasopharyngeal Carcinoma Patient in General Hospital Haji Adam Malik Medan : A Case Report - Saurma Otri Sonya Simanjuntak; Farhat Farhat; Elvita Rahmi Daulay (TALENTA PUBLISHER, 2021)
Introduction: Nasopharyngeal carcinoma (NPC) is in the fourth place according to the most most common malignancies in Indonesians. Three types of nasopharyngeal carcinoma are squamous cell, non-keratinizing, and undifferentiated carcinoma. Case report: A 51-year-old man came to the ENT-Head and Neck Surgery Outpatient clinic of General Hospital Haji Adam Malik Medan on November 2, 2020 with main complaint of lump on the neck and nasal congestion. The patient underwent a contrast-enhanced nasopharyngeal MSCT scan with the result: T2N0M0. The histopathology results: Non-Keratinizing Squamous Cell Carcinoma. The patient was given 70 gy of Chemoradiation (CRT) followed by adjuvant chemotherapy with Cisplatin + 5 Fu. Conclusion: There was no visible mass on the nasopharynx after using this combination therapy